2018
DOI: 10.1002/ente.201700885
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Impregnation Processes on Ruthenium–Molybdenum Carbon Catalysts for Selective Hydrodeoxygenation of Biomass‐Derived Sorbitol into Renewable Alkanes

Abstract: Sorbitol, as a C6 sugar related compound derived from cellulose, is regarded as a promising biomass‐derived substrate and has characteristically higher oxygen content than in fossil‐based resources. In this work, ruthenium–molybdenum carbon catalysts prepared by different impregnation processes were employed and extensively studied in a trickle‐bed reactor for sorbitol hydrodeoxygenation (HDO). Interestingly, these catalysts afforded remarkably different HDO performance. Ruthenium–molybdenum catalysts prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Ru/C showed a main peak below 400 °C, and Mo/C gave a big peak above 500 °C. While, RuMo/C presented abig peak located at a slightly higher temperature than that of Ru/C catalyst, and the peak assignable to Mo species was nearly disappeared, which suggested that the reduction of Mo species could be promoted by the presence of Ru via H 2 spillover [17,20,21,23,40]. The evaluated value of Mo species based on the H 2 consumption was determined about + 4, which was also supported by XPS result.…”
Section: Figsupporting
confidence: 53%
See 4 more Smart Citations
“…Ru/C showed a main peak below 400 °C, and Mo/C gave a big peak above 500 °C. While, RuMo/C presented abig peak located at a slightly higher temperature than that of Ru/C catalyst, and the peak assignable to Mo species was nearly disappeared, which suggested that the reduction of Mo species could be promoted by the presence of Ru via H 2 spillover [17,20,21,23,40]. The evaluated value of Mo species based on the H 2 consumption was determined about + 4, which was also supported by XPS result.…”
Section: Figsupporting
confidence: 53%
“…S2. Unfortunately, no obvious difference was observed among the catalysts due to the amorphous property of AC and fine particles size [23,31,37]. Moreover, Raman spectra of samples were also supported in Fig.…”
Section: Catalyst Characterizationmentioning
confidence: 66%
See 3 more Smart Citations